In vitro propagation of cryptocoryne ferruginea engler - Chen, Mei Yin (Universiti Malaysia Sarawak (UNIMAS), 2012)
Cryptocoryne ferruginea Engler (Araceae) is an endemic species of Borneo. Many Cryptocoryne species are popular as aquarium plants but there is limited information on the successful commercialization of the species from Malaysia. Surface sterilization using 70 % ethanol for 1 minute, 15 % (v/v) Clorox® for 15 minutes and rinsed thrice with distilled water produced the highest percentage of contamination-free petiole explants at 50 %. For runner explants, 15% (v/v) Clorox® for 12 minutes produced 58% contamination-free runner explants during the first two weeks after culture initiation in Murashige & Skoog (MS) medium. Only 4 explants (4.17 %) runner explants remained uncontaminated after four weeks. Incorporation of Plant Preservative Mixture (PPM™) into MS medium reduced contamination up to 100% in runner explants but only 5 explants (5.21%) were viable for shoot regeneration. The protocol requires further refinement to improve its efficiency. Multiple shoot, leaf and root regeneration used combinations of BAP (0-2.0 mg/L) with or without 0.1 mg/L IBA. Highest mean number of shoots (6.93) and leaves (3.33) per explant was observed in medium supplemented with 1.0mg/L BAP and 0.1mg/L IBA. Addition of 0.1mg/L IBA alone induced highest mean number of roots (2.93) per explant. Different medium (solid or liquid) with or without 0.1 mg/L NAA was used for root induction. Highest mean number of roots (4.25) per explant was induced in liquid medium supplemented with 0.1 mg/L NAA.